THE HUGGER-MUGGER OF ENFORCING SOCIO-ECONOMIC RIGHTS IN GHANA: A THREAT TO THE RIGHTS OF PERSONS WITH DISABILITIES (African Disability Rights Yearbook, 2021)
At the heart of the Convention on the Rights of Persons with Disabilities (CRPD) is the reaffirmation of the universality, indivisibility, interdependence and interrelatedness of all human rights, and the open acknowledgement that civil and political rights alone cannot fully protect the inherent dignity and worth of persons with disabilities. Accordingly, the aims of the CRPD cannot be realised unless the socio-economic rights of persons with disabilities are rigorously enforced. Ghana, like most African signatories to the CRPD, operates a human rights regime that pays little attention to socio-economic rights. Socio-economic rights are contained in Chapter VI of Ghana’s Constitution (1992). The Chapter, titled the ‘Directive Principles of State Policy’, has been interpreted by its Supreme Court variously, making it impossible to discern, clearly, whether the rights listed in the Chapter are justiciable. These inconsistent interpretations pose a major challenge to the full implementation of the CRPD. This article seeks to achieve three broad objectives: to explain why socio-economic rights have been effectively unenforceable in Ghana; to show how the current situation poses a threat to the full performance of Ghana’s obligations under the CRPD; and to propose some ways of going round the impasse. The article is divided into five parts. Part 1 offers a brief description of the landscape of disability in Ghana. Part 2 unpacks the nature of the obligation that states undertake when they ratify the CRPD. It also explains how these obligations cannot be fully performed unless socio-economic rights are rigorously enforced. Part 3 takes a critical look at Ghana’s human rights regime under the 1992 Constitution. Part 4 will conduct a brief international comparative analysis on how two countries - India and South Africa - have enforced socio-economic rights. The final Part will conclude by drawing on the experiences from other jurisdictions to suggest mechanisms for going round the impasse.